المعنى الصرفي ودوره في بناء القصدية دراسة نصية في المقامة البغدادية للهمذاني - بوبكر عباس; محمود رداد (University of Eloued جامعة الوادي, 2025)
تُعدّ القصدية معيارا مهما من معايير الدراسات النصية اللسانية الحديثة، حيث تهتم بمقاصد منتج النص، حيث درسنا في هذا الموضوع تجليات القصدية في المقامة البغدادية لبديع الزمان الهمذاني، حيث كشف البحث عن العديد من الشواهد الصرفية التي تدل على تحوّل المعنى المعجمي إلى بنية قصدية إيحائية يستشفها القارئ في ثنايا سياق النص، وقد تنوعت هذه البنى الصرفية في الأفعال المزيدة بين المزيد بحرف والمزيد بحرفين والمزيد بثلاثة أحرف، وهي بنى متفرقة مبعثرة لكنها تنصهر في بوتقة واحدة لتؤسس لقصدية دلالية محكمة تقود القارئ إلى معناها الإيحائي الذي يعيد إنتاجه وصياغته من وعيه الخلاق بناء على التأويل والتخييل المستند إلى المعرفة الثقافية بالواقع والتاريخ. Intentionality is considered a crucial criterion in modern textual linguistic studies, focusing on the intentions of the text's creator. In this context, we studied the manifestations of intentionality in Al-Baghdadi’s Maqamat by Badi' al-Zaman al-Hamadhani. The research revealed several morphological instances indicating the transformation of lexical meaning into an intentional, suggestive structure that the reader infers from the context of the text. These morphological structures varied in the derived verbs, including those with one, two, and three additional letters. While these structures are scattered and distinct, they merge into a cohesive whole that establishes a well-structured semantic intentionality, guiding the reader to its suggestive meaning. This meaning is then reinterpreted and restructured by the reader’s creative consciousness, based on the process of interpretation and imagination, which is grounded in cultural and historical knowledge of reality..
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: لسانيات النص، القصدية، المقامة البغدادية، أبنية المزيد; Text linguistics. Intentionality. Al-Baghdadi’s Maqama. Derived verb structures.